Electrophoretic characterization of clay mineral systems for smectite recovery - Manapat, Jill Z.
The Philippines is currently importing smectite for research purposes, but a study by Bernard et. al. showed that San Nicolas clay from Ilocos Norte, Philippines is rich in smectite and kaolinite. The usual low-cost technique employed for clay separation is sedimentation. However, the process is time consuming and the resulting purity of the recovered clay is not enough for research applications. This study aims to use the electrophoretic behavior of smectite and kaolinite clay minerals to define conditions that will allow their separation in a synthetic system. If successful, this novel technique for separation can add value to the indigenous clay resource available in the Philippines. Zeta potential measurements showed that pH has negligible effect on the electrophoretic mobility of smectite, but has an appreciable effect on the mobility of kaolinite with the isoelectric point (IEP) of kaolinite recorded around pH 5. Knowing this behavior, EPD of a 3.5wt% smectite-kaolinite slurry was carried out at pH 5 and pH 10. Separation of clay minerals was expected only at pH 5 where kaolinite is almost immobile. However, analysis of deposits using XRD and EDX showed some degree of separation for both pH values when EPD was performed using stainless steel electrodes at a specific applied voltage and electrode gap, for twenty minutes, without stirring. The quality of the deposit in terms of yield and adhesion to the electrode was better at high pH. It was shown that EPD is indeed a promising technique for upgrading the quality of local clay, but further study is needed to improve EPD design for more efficient recovery.